Thermo-elastic strain analysis in crystallographic-texture-aligned Fe–Pd magnetic shape memory alloy. (1st July 2019) - Han, Jun Hyun; Han, Taeyang; Sohn, Youhan; Kim, Dong-Ik; Kim, Hye Sung; Jin, Sungho
Abstract: We examined the effect of the crystallographic texture on the thermo-elastic strain of polycrystalline Fe–Pd magnetic shape memory alloy (MSMA) thin films that were sputter-deposited in the presence of a magnetic field. The thermo-elastic strain of an Fe–27.8 at% Pd film sputtered in the presence of a magnetic field was more than six times larger than that of a film deposited without magnetic field. We attribute the increased thermo-elastic strain to a shift in the crystallographic texture; from a 〈111〉 fiber texture for films deposited without magnetic field to a {113}〈411〉 texture for films deposited with magnetic field. Graphical abstract: Unlabelled Image